How do you solve sec^2(x) - sec(x) = 2sec2(x)sec(x)=2?

1 Answer
Dec 4, 2015

x= \pi + 2k\pix=π+2kπ

x = \pi/3 + 2k\pix=π3+2kπ

x= -pi\/3 + 2k\pix=π3+2kπ

Explanation:

Since sec(x)=1/cos(x)sec(x)=1cos(x), the expression becomes

1/cos^2(x) - 1/cos(x) = 21cos2(x)1cos(x)=2

Assuming cos(x)\ne 0cos(x)0, we can multiply everything by cos^2(x)cos2(x):

1-cos(x) = 2cos^2(x)1cos(x)=2cos2(x).

Rearrange:

2cos^2(x)+cos(x)-1=02cos2(x)+cos(x)1=0.

Set t=cos(x)t=cos(x):

2t^2+t-1=02t2+t1=0

Solve as usual with the discriminant formula:

t=-1t=1, t=1/2t=12

Convert the solutions:

cos(x)=-1 \iff x=\pi+2k\picos(x)=1x=π+2kπ

cos(x)=1/2 \iff x=\pm\pi/3 +2k\picos(x)=12x=±π3+2kπ